Effect of pre-harvest and post-harvest conditions and treatments on plum fruit quality - Vicente, Ariel Roberto; Crisosto, Carlos H.; Manganaris, George A. (My University, 2008)
Plums belong to the Rosaceae family and include the European species (Prunus domestica L.), which is consumed fresh or dried, and the Japanese species (Prunus salicina Lindell), mainly freshly consumed. Plums are considered climacteric, although some plum cultivars do not show the typical increase in ethylene production and respiration until late ripening. They respond to exogenous ethylene, which is a key ripening regulator, while treatments with 1-methylcyclopropene (1-MCP), an ethylene action inhibitor, are effective in delaying fruit ripening. Plum fruit is characterized by high softening rate and, so far, the sequence of events leading to cell wall degradation, as well as changes in the proteins responsible for these modiﬁcations, has not been thoroughly investigated. Post-harvest diseases (brown rot, grey mould and Rhizopous rot) are also a main concern in plum post-harvest handling and storage. Prompt cooling and low-temperature storage (0 C) are recommended to delay ripening and maintain plum fruit quality. However, when the fruit is held for long periods at low temperature, chilling injury (CI) symptoms, usually manifested as translucency, bleeding, ﬂesh browning and/or failure to ripen, might develop. Although softening can be delayed by controlled and modiﬁed atmospheres, this technology is not widely used commercially, since the beneﬁts are not as pronounced as in other fruit species. Other post-harvest strategies tested to date with apparent usefulness at a laboratory scale include heat treatment, ozone, polyamine and calcium treatments, as well as fumigation with environmentally friendly compounds; such strategies might be useful under particular circumstances to complement other post-harvest treatments. Pre-harvest treatments, such as application of synthetic auxins and calcium, regulation of canopy light conditions and orchard soil management, have been reported to affect plum fruit quality and its post-harvest behaviour. Overall, the present review discusses the inﬂuence of ﬁeld and post-harvest practices on plum fruit quality and market life.
Keywords: Plum; Harvesting; Fruit--Quality; Fruit--Ripening